Assessment and Analysis of Writing Activities of Secondary High School English Textbooks: Vision Series - Esmael Abbasi; Abdullah Sarani; Mehdi Mohammadi Nia (Iranian Journal of Applied Language Studies, 2021)
Writing is one of the four skills of language learning, especially, one of the skills of practical communication in a communicative approach. The purpose of this research is to evaluate and analyze writing activities of the writing sections of secondary high school English textbooks, grades 10th, 11th and 12th, so-called vision 1, 2, 3. The theoretical framework of this research, a descriptive-analytical and qualitative method, was based on Kern's (2007) and Harmer’s (2004) model and continuum of writing activities. The writing activities of these vision books were divided into three major categories of controlled, guided and free writing and fifteen more sub-categories. The exercises and activities of the writing section of these six-volume English textbooks, so-called vision 1,2,3 were counted on and the average and percentage of each category were calculated based on Kern’s (2002) and Harmer’s (2004) model and continuum of writing. The findings of this research indicate that the categories of controlled writing and copying, the first item of Kern’s continuum, are the dominant writing tasks in these books. Activities concerning the guided, and especially the free writing activities in these books are rarely seen or they have not been much carefully regarded. In the communicative approach, regarding the goods and the existing requirements, the teaching of writing is generally concerned with free writing tasks. Therefore, to enhance and promote practical communication skills as an aim of a communicative approach, free writing skills are inevitable. The findings of this research point out that English teachers can reinforce and enhance their students’ practical communication abilities in their classes by using freestyle exercises and hence, cover the shortcomings of the books.